The rising cost of European Union borrowing and what to do about it - Gregory Claeys; Conor McCaffrey; Lennard Welslau (Bruegel, 2023)
Debt issuance by the European Commission on behalf of the European Union has increased massively. Of the approximately exteuro400 billion in outstanding EU debt as of May 2023, 85 percent has arisen from borrowing since 2020. Large-scale borrowing is expected to continue until 2026 to fund the remainder of NextGenerationEU, and concessional loans to support Ukraine. When these programmes were launched, interest rates were at historic lows - even negative for maturities below 10 years. However, interest rates rose sharply in 2022. Beyond the widespread rise in euro-denominated interest rates due to monetary tightening by the European Central Bank in response to the inflation surge, the EU has also faced a widening of the spread between its yields and those of major European issuers, including France and Germany. This widening is driven by a combination of market features, circumstantial factors and institutional features. The EU cannot affect the overall cyclical movement of interest rates and will have to learn to live with it, like sovereigns do. However, the European Commission should continue to try to narrow the spread with major European sovereigns by further developing the relevant market infrastructure and improving its issuance strategy. The Commission will not be able to do this alone. Institutional developments, including progress on the development of new own resources and a long-term substantial presence in the bond market, will be necessary to fully reap the benefits of EU borrowing. A large share of EU borrowing (around exteuro421 billion in total by the end of 2026, in current prices) is intended to finance unprecedented non-repayable support: Recovery and Resilience Fund grants and additional funding for existing EU programmes under the EU budget. The interest costs associated with this part of the debt lie with the EU budget. Our estimates suggest that, because of the high current and expected levels of interest rates, this cost could be twice as high as what was initially estimated at the start of the EU's 2021-27 budget cycle. As a result, because interest costs for the borrowing of the non-repayable support are accounted for under the EU budget's 'expenditure ceiling', this will exert further pressure on the funding of important EU programmes, which are already affected by inflation. The EU should thus quickly review how interest costs are accounted for in its budget and financial framework.
Keywords: 330